The theology of the book of Amos. - Barton, John 1948- (Cambridge Cambridge university press, 2012)
"In modern times Amos has come to be considered one of the most important prophets, mainly for his uncompromising message about social justice. This book provides a detailed exploration of this theme and other important elements of the theology underlying the book of Amos. It also includes chapters on the text itself, providing a critical assessment of how the book came to be, the original message of Amos and his circle, which parts of the book may have been added by later scribes, and the finished form of the book. The author also considers the book,Ŵs reception in ancient and modern times by interpreters as varied as rabbis, the Church Fathers, the Reformers, and liberation theologians. Throughout, the focus is on how to read the book of Amos holistically to understand the organic development of the prophet,Ŵs message through the many stages of the book,Ŵs development and interpretation"--Provided by publisher.
"This book provides a detailed exploration of the important elements of the theology underlying the book of Amos"--Provided by publisher.
Machine generated contents note: General editors' preface; Preface; 1. Amos: the critical issues; 2. Religious belief and practice in Amos's day; 3. The theology of Amos and his circle; 4. Theological theme in the additions to the book of Amos; 5. The theology of the book of Amos; 6. The reception of the theology of Amos; 7. The theology of Amos then and now.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Theology; 224.63 -- Amos